Adjustment of profits: Evidence from Australian manufacturing - Bhattacharya, M.; Bloch, Harry (Kluwer, 2000)
Studies of industry profitability generally deal with long-run equilibrium models, making no allowance for slow adjustment to equilibrium. In this study, a cross-sectional analysis is carried out against a sample of Australian manufacturing industries at the Australian Standard Industrial Classification (ASIC) four-digit level between 1977-78 and 1984--85. Firstly, a profit model is estimated in equilibrium form as well as allowing for both uniform and variable adjustment rates across industries. The variable adjustment model is superior, with either model implying at least half adjustment to equilibrium within the seven-year sample period. Secondly, results are examined for the impact of firm homogeneity of firms within industries. Homogeneity of firms is found to havesubstantial impact, increasing both the estimated profits-concentration relationship and the estimated speed of adjustment.